Peran Green Accounting dan Green Intellectual Capital terhadap Nilai Perusahaan - Manan, Mohammad Athian; Wuryanti, Lestari; Mufahamah, Euis (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to investigate the effect of Green Accounting and Green Intellectual Capital on the firm value of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Methodology/approach: This research adopts a descriptive quantitative approach, utilizing secondary data obtained from annual and sustainability reports. The study population comprises 134 manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. A total of 94 firms were selected using purposive sampling based on specific criteria. Data analysis is performed using SPSS version 23, applying panel data regression methods. Firm value is represented by Tobin’s Q, Green Accounting is evaluated through environmental disclosure indicators, and Green Intellectual Capital is measured using human, structural, and relational capital proxies. Results/findings: The findings indicate that both Green Accounting and Green Intellectual Capital have a positive and significant effect on firm value. These results suggest that companies that are transparent about environmental practices and strategically manage intellectual resources are better valued in the market. Conclutions: Green Accounting and Green Intellectual Capital have a significant positive impact on firm value. Environmental transparency and effective management of intellectual resources enhance market perception, reflecting higher value for manufacturing firms in Indonesia during the 2019–2023 period. Limitations: The study only focused on listed manufacturing companies and used publicly available secondary data. Contribution: This research enriches the understanding of sustainability practices' role in increasing firm value, especially in emerging markets.